IMPLEMENTATION OF BPJS KESEHATAN COOPERATION AGREEMENT WITH HEALTH FACILITIES IN ENSURING FAIR ACCESS TO HEALTH SERVICES - Rahmad Hidayat Harahap; Suparto; Surizki Febriyanto (Hukum Responsif, 2026)
Health is a constitutional right of citizens that must be guaranteed by the state through the provision of fair and equitable health services. In the implementation of the National Health Insurance Program (JKN), BPJS Kesehatan collaborates with various health facilities through cooperation agreements as the basis for providing health services to participants. However, the implementation of the agreement still faces various problems, such as inequality in the position of the parties, delay in payment of claims, limited health facilities, and disparity in service quality between regions that have the potential to affect the fairness of access to health services for the community. This study aims to analyze the implementation of the cooperation agreement between BPJS Kesehatan and health facilities in the implementation of JKN, examine its effectiveness in ensuring fair access to health services, and formulate efforts to strengthen the implementation of the agreement. This research is a normative legal research using a statute approach, a conceptual approach, and a case approach. The data used are in the form of primary legal materials and secondary legal materials that are analyzed qualitatively through descriptive-analytical methods. The results of the study show that the implementation of BPJS Kesehatan cooperation agreements with health facilities has played an important role in expanding the scope of health services and increasing public access to health services. Its effectiveness in realizing fair access to health services still faces various obstacles, especially related to the uneven distribution of health facilities, the limitation of health workers, and the imbalance in contractual relations between BPJS Kesehatan and health facilities. Therefore, it is necessary to strengthen regulations, reformulate cooperation agreement clauses, increase the transparency of claim payments, and strengthen supervision and equity in health facilities to support the realization of fair access to health services for the entire community.